The fashion gap: the Cold War politics of American and Soviet fashion, 1945-1959. (15th February 2016) - Amerian, Stephanie M.
Abstract : Purpose: – The purpose of this paper is to examine the role that fashion played in the Cold War competition between the USA and the Soviet Union during the period from 1945 to 1959. Design/methodology/approach: – This paper begins by situating fashion within the larger American efforts of cultural diplomacy. It then examines the American and Soviet approaches to fashion. Finally, it focuses on the fashion show at the 1959 American National Exhibition in Moscow. This paper utilizes primary sources, including archival sources and period newspapers and magazines. Findings: – Both American and Soviet leaders tried to use fashion to embody the ideological values of each political and economic system. Both also acknowledged a "fashion gap", whereby Americans enjoyed clear superiority thanks to a well-developed mass production system of ready-made, stylish clothing, that some termed the American Look. Americans hoped the fashion gap would demonstrate that only capitalism could provide women with an abundance of the necessary – but also desirable – consumer goods that enhanced their feminine beauty. Thus, fashion played an important part in the Cold War cultural struggle, in which American and Soviet women were key participants. Originality/value: – Much has been written about the Cold War cultural diplomacy, especially the Moscow exhibition, but fashion is often left out of the analyses. Meanwhile, both the American Look and Soviet efforts to create socialist fashion have been examined, but no work has been done to look at the two together to understand fashion's larger implications for the Cold War.